Molecular interactions between the soilborne pathogenic fungus Macrophomina phaseolina and its host plants - Shirai, Miwa; Eulgem, Thomas (Frontiers in Plant Science, 2023)
Mentioned for the first time in an article 1971, the occurrence of the term "Macrophomina phaseolina" has experienced a steep increase in the scientific literature over the past 15 years. Concurrently, incidences of M. phaseolinacaused crop diseases have been getting more frequent. The high levels of diversity and plasticity observed for M. phasolina genomes along with a rich equipment of plant cell wall degrading enzymes, secondary metabolites and putative virulence effectors as well as the unusual longevity of microsclerotia, their asexual reproduction structures, make this pathogen very difficult to control and crop protection against it very challenging. During the past years several studies have emerged reporting on host defense measures against M. phaseolina, as well as mechanisms of pathogenicity employed by this fungal pathogen. While most of these studies have been performed in crop systems, such as soybean or sesame, recently interactions of M. phaseolina with the model plant Arabidopsis thaliana have been described. Collectively, results from various studies are hinting at a complex infection cycle of M. phaseolina, which exhibits an early biotrophic phase and switches to necrotrophy at later time points during the infection process. Consequently, responses of the hosts are complex and seem coordinated by multiple defense-associated phytohormones. However, at this point no robust and strong host defense mechanism against M. phaseolina has been described.